Students’ Emotions in Online Learning Post-Covid-19 : A Study of Malaysian University Students - Salinayanti, Salim; Christie Andharea, Sabli (Unimas Publisher, 2025)
This study explores the emotional experiences of the students in a Malaysian universityin online learning post-COVID-19. The pandemic forced a shift from traditional to online learning, leading to various emotional responses among students. However, there is limited understanding of how these emotional responses impact students’ engagement and learning satisfaction in the Malaysian context. A survey of 121 students revealed mixed feelings. While some appreciated the flexibility and comfort of learning from home, others faced anxiety, boredom, and challenges with maintaining focus and motivation. The study found that students enjoyed certain aspects of online learning, such as recorded lectures, but struggled with engagement and technical issues. The findings highlight the need for more interactive and supportive online learning environments to enhance student satisfaction and learning outcomes